A EUROPEAN DEFENSE FORCE: A COMPREHENSIVE APPROACH TO STABILITY AND PROGRESS. THE ECONOMIC PERSPECTIVE - Cristian Romeo SPĂTARU; Cristian Constantin POPESCU (Annals of the University of Oradea: Economic Science)
The EU is an undeniable economic and civil-normative power. Military force is a key element of “hard power.” Stability is a prerequisite for development, and a strong army is a guarantor of stability. This analysis will explore the advantages and challenges of establishing a common European army, focusing on available resources (cultural-historical, economic, and military). Success requires financial resources. We will emphasize the need for an opportunity to create a common army. There will be no lack of infrastructure, innovation, and defense technologies, along with the presentation of potential economic benefits. While external threats can speed up the process, a lack of consensus and slow progress in the CFSP hamper its realization.